Effect of Fe3O4-magnetic nanoparticles on acute exercise enhanced KCNQ1 expression in mouse cardiac muscle - Lijie Liu (Dove Medical Press, 2010)
Lijie Liu1, Baoan Chen2, Feixiang Teng1, Lijuan Shi1, Nan Jing2, Li Wang1, Ningna Chen2, Guohua Xia2, Xiaomao Li31Department of Physiology and Pharmacology, Medical School, Southeast University, Nanjing, People’s Republic of China; 2Department of Hematology, Affiliated Zhongda Hospital, Clinical Medical School, Southeast University, Nanjing, People’s Republic of China; 3Department of Physics, University of Saarland, Saarbruechen, GermanyAbstract: While the potential impact of magnetic nanoparticles (MNPs) has been widely explored in almost all medical fields, including cardiology, one question remains; that is whether MNPs interfere with cardiac physiological processes such as the expression and function of ion channels, especially in vivo. KCNQ1 channels are richly expressed in cardiac myocytes and are critical to the repolarization of cardiac myocytes. In this study, we evaluated the effects of Fe3O4-magnetic nanoparticles (MNPs-Fe3O4) on the expression of KCNQ1 in cardiac muscle of mice at rest and at different times following a single bout of swimming (SBS). Firstly, we demonstrated that the expression levels of KCNQ1 channels are significantly up-regulated in mice following a SBS by means of reverse transcription polymerase chain reaction (RT-PCR) and western-blot. After treating mice with normal saline or pure MNPs-Fe3O4 separately, we studied the potential effect of MNPs-Fe3O4 on the expression profile of KCNQ1 in mouse cardiac muscle following a SBS. A SBS increased the transcription of KCNQ1 at 3 hours post exercise (3PE) 164% ± 24% and at 12 hours post exercise (12PE) by 159% ± 23% (P < 0.05), and up-regulated KCNQ1 protein 161% ± 27% at 12PE (P < 0.05) in saline mice. In MNPs-Fe3O4 mice, KCNQ1 mRNA increased by 151% ± 14% and 147% ± 12% at 3 and 12 PE, respectively (P < 0.05). Meanwhile, an increase of 152% ± 14% in KCNQ1 protein was also detected at by 12PE. These results indicated that the administration of MNPs-Fe3O4 did not cause any apparent effects on the expression profile of KCNQ1 in rested or exercised mice cardiac muscle. Our studies suggest a novel path of KCNQ1 current adaptations in the heart during physical exercise and in addition provide some useful information for the biomedical application of MNPs which are imperative to advance nanomedicine.Keywords: KCNQ1, cardiac muscle, magnetic nanoparticles of Fe3O4